A guide on empirical tests of the EMH. Issue 2 (22nd March 2019) - Peón, David; Antelo, Manel; Calvo, Anxo
Abstract : Purpose: The efficient market hypothesis (EMH) states that asset prices in financial markets always reflect all available information about economic fundamentals. The purpose of this paper is to provide a guide as to which predictions of the EMH seem to be borne out by empirical evidence. Design/methodology/approach: Rather than following the classic three groups of tests for the different forms of EMH that are common in the literature, the authors consider how the two alternative definitions of the EMH and the joint hypothesis problem impact on the tests and leave the controversy unsolved. The authors briefly report the antecedents, the main theoretical and empirical contributions and recent literature on each type of tests. Findings: Eventually, as a summary for each type of tests, the authors provide a critical view on the main sources of acrimony between the alternative schools of thought in understanding asset price formation. Originality/value: The paper may be seen as an up-to-date introductory review for researchers on the different tests of the EMH performed, and for newcomers to understand the key sources of acrimony between rationalists and behaviorists.